Evaluation of the treatment of II and III degree hemorrhoids: A comparison of mucosa suspension procedure for prolapse and hemorrhoids, Shenyang city, China, 2006-2009 - Song, Duo; Dai, Xian wei; Chen, Chun sheng (Colombia Medica, 2024)
Objective: The aim of this study was to evaluate the effect of mucosa suspension procedure (MSP) by comparing procedure for prolapse and hemorrhoids (PPH). Methods: We compared the safety, clinical outcome, and cost between PPH and MSP for the surgical treatment of hemorrhoidal disease. A total of 80 patients with II and III degree hemorrhoids were included in the study. MSP group (n=40) and PPH group (n=40) were applied at random. Results: Both MSP and PPH are safe surgical treatments for patients with II and III degree hemorrhoids. Complications of the patients, such as persistent pain and tenesmus in the MSP group were less than the PPH group. Moreover, MSP had lower costs. Conclusion: MSP is a safe, effective, and inexpensive procedure for patients with hemorrhoidal disease. We consider that this technique should be widely used.